Effect of addition of CuO and Bi2O3 on Low sintering of Pb(Zr,Ti)O3-PbZn1/3Nb2/3O 3-(Ni1/3Nb2/3)O3 based ceramics - Athipong Ngamjarurojana (2018)
In this study, in order to develop low-temperature-sintering ceramics for a multilayer piezoelectric transformer application, we explored CuO and Bi2O3 as sintering aids Pb(Zr,Ti)O3-PbZn1/3Nb2/3O 3-(Ni1/3Nb2/3)O3-(PZT-PZN-PNN) based ceramics with excellent piezoelectric and dielectric properties such as d 33 ∼ 347 pC/N,kp ∼ 0.57, and Qm ∼ 1469. The addition of CuO decreased the sintering temperature through the formation of a liquid phase. However, the piezoelectric properties of the CuO-added ceramics sintered below 900 °C were lower than the desired values. The additional Bi2O3 resulted in a significant improvement in the piezoelectric properties. At the sintering temperature of 900oC, the electromechanical coupling factor (kp),piezoelectric constant (d33), mechanical quality factor (Qm) of PZT-PZN-PNN composition ceramics with addition of 0.5 wt% CuO and 0.5 wt% Bi2O3 showed the optimal value of 0.56, 350 pC/N, and 1042, respectively. These values indicated that the newly developed composition may be suitable for multilayer piezoelectric transformer application.